2004
DOI: 10.1111/j.1440-1754.2004.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Arterial ischaemic stroke in children

Abstract: AIS is over-represented in children under 12 months of age and results in death or residual neurological impairment in the majority of cases. Further prospective studies are needed to identify risk factors for poor outcome. The recently established Australian and New Zealand Stroke and Thrombophilia Registry should provide important information on clinical and laboratory based risk factors and create a basis for international clinical trials to improve the outcome of childhood AIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
34
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 19 publications
11
34
1
2
Order By: Relevance
“…218,717,718 The overall risk of a recurrent AIS and TIA is 10% to 35%. 413,415,[719][720][721][722][723][724][725][726][727][728][729] The recurrence risk increases in the presence of multiple stroke risk factors. 726 Genetic thrombophilia was previously reported as increasing the recurrence rate 725 ; however, a more recent comprehensive study suggested that this is not the case.…”
Section: Cerebral Vasculopathiesmentioning
confidence: 99%
“…218,717,718 The overall risk of a recurrent AIS and TIA is 10% to 35%. 413,415,[719][720][721][722][723][724][725][726][727][728][729] The recurrence risk increases in the presence of multiple stroke risk factors. 726 Genetic thrombophilia was previously reported as increasing the recurrence rate 725 ; however, a more recent comprehensive study suggested that this is not the case.…”
Section: Cerebral Vasculopathiesmentioning
confidence: 99%
“…1 Mortality risk because of AIS in children is 6% to 8%, 2 and ϳ 75% suffer long-term neurologic deficits. 3,4 Recurrence rates for AIS and transient ischemic attack (TIA) in non-neonate children are 16% to 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported potentially beneficial effects of ACT at therapeutic or prophylactic doses in treating children with AIS. 2,[7][8][9][10][11] Consensus-based pediatric treatment guidelines [12][13][14] suggest that both anticoagulation and ASA are reasonable initial considerations in childhood AIS. However, the evidence base for this is minimal (2C or class II), 12,13 including lack of adequate safety data for ACT.…”
Section: Introductionmentioning
confidence: 99%
“…больных с ИИ доля кардиоэмболического инсульта (КЭИ) в свою очередь составляет 10-31% [5][6][7][8][9][10]. Несмотря на хорошо известную и кажущуюся по-нятной связь церебральной сосудистой патологии и тяжелых болезней сердца, КЭИ у детей до сих пор является диагностической проблемой.…”
unclassified